Effect of Shang-tune music on the relief of negative emotions in patients with chronic obstructive pulmonary disease and its influencing factors (商调音乐改善慢性阻塞性肺疾病患者负面情绪的效果及其影响因素分析) - XIE Xiaomin (谢小敏); ZHANG Yanmei (张焱梅); PAN Tiantian (潘甜甜); CAO Jing (曹静); YU Wenwen (於雯雯); WU Jingjing (吴静静); ZHAO Huan (赵焕) (中西医结合护理)
Objective To investigate the effect of Shang-tune music on the relief of negative emotions in patients with chronic obstructive pulmonary disease (COPD), and to analyze potential factors influencing the efficacy of the intervention. Methods A prospective research method was adopted, and totally 120 COPD patients were recruited in the study. All patients received the Shang-tune music intervention during hospital stay, and extended care with telephone was used to improve patients’ compliance with music therapy during follow-up, lasting for 12 weeks. The COPD Assessment Test(CAT) was used the assess the severity of illness. Hamilton Depression Scale(HAMD) and Hamilton Anxiety Scale(HAMA) were used to assess the emotional status of patents. A logistic regressive method was conducted to analyze the potential factors influencing the efficacy of the intervention. Results The HAMA and HAMA scores decreased after a 12-week intervention of Shang-tune music therapy(P＜0. 01). There was a significant difference in proportion of patients who diagnosed as anxious/depressive disorders before and after intervention (P＜0. 01). Logistic regression analysis showed that course of disease, extrovert personality, high education level, knowledgeable about music, family support and CAT score were factors influencing the intervention effect on relief of depression(P＜0. 05), and patients receiving Shang-tune music therapy had an odds ratio of 3. 325(95% CI: 0. 876-36. 158, P＜0. 01) for relief of depression. Logistic regression analysis showed that extrovert personality, knowledgeable about music, family support and CAT score were factors influencing the intervention effect on relief of anxiety(P＜0. 05), and patients receiving Shang-tune music therapy had an odds ratio of 2. 825(95% CI: 0. 853-32. 268, P＜0. 01) for relief of anxiety. Conclusion The Shang-tune music is effective to relieving the anxiety and depression of COPD patients. Personal characteristics, education level, knowledge about music, family support and CAT scores were potential factors influencing the implementation of Shang-tune music therapy. (目的 探讨商调音乐改善慢性阻塞性肺疾病(COPD)患者抑郁及焦虑状态的效果, 并分析可能的影响因素。方法 采用前瞻性研究方法, 收集医院2019年1月—2021年7月呼吸中心住院的COPD患者120例, 住院期间给予商调音乐干预, 出院后采用定期电话回访方式督促其坚持音乐疗法, 干预12周为1个疗程。收集患者一般资料, 并采用慢性阻塞性肺病评估测试(CAT)来评价患者疾病严重程度, 同时采用汉密尔顿抑郁量表-17项(HAMD)、汉密尔顿焦虑量表(HAMA)来评价患者抑郁及焦虑状态改善情况, 最后采用logistic回归分析评价商调音乐干预效果的影响因素。结果 干预后, 患者HAMD评分和HAMA评分较干预前下降, 差异有统计学意义(P＜0. 01); 干预前后抑郁症、焦虑症占比, 差异具有统计学意义(P＜0. 01)。Logistic回归分析显示: 影响商调音乐对抑郁情绪改善效果的因素包括: 病程、性格(外向)、文化程度(高中以上)、音乐知识(丰富)、家庭支持及CAT评分(P＜0. 05), 商调音乐对抑郁情绪改善的OR为3. 325(95% CI: 0. 876-36. 158, P＜0. 01)。影响商调音乐对焦虑情绪改善效果的因素包括: 性格(外向)、音乐知识(丰富)、家庭支持及CAT评分(P＜0. 05), 商调音乐对焦虑情绪改善的OR值为2. 825(95% CI: 0. 853-32. 268, P＜0. 01)。结论 商调音乐能有效缓解COPD患者抑郁、焦虑等负面情绪, 性格、音乐知识、家庭支持及CAT评分为影响商调音乐干预效果的因素。)